Eosinophilic esophagitis manifesting as intractable hiccups in an elderly patient: a case report - Sarah Jalloul; Johny Salem; Karam Karam; Clara Chamoun; Louis Chaptini (Journal of Medical Case Reports, 2025)
Abstract Background Eosinophilic esophagitis is a condition characterized clinically by symptoms related to esophageal dysfunction and histologically by a marked eosinophilic infiltrate in the esophageal mucosa. The most typical symptoms of eosinophilic esophagitis include intermittent dysphagia with episodic food impaction and heartburn with propensity for young individuals. The relationship between hiccups and eosinophilic esophagitis is unclear but has been described. Case report We report a case of a 93-year-old Middle Eastern male presenting for longstanding treatment-refractory hiccups. Imaging with computed tomography of the chest and abdomen was unremarkable. An upper endoscopy was normal without any endoscopic finding to suggest eosinophilic esophagitis. Given his elevated peripheral eosinophil count, biopsies were taken from mid- and distal esophagus and revealed eosinophilic infiltration in the range of 15 eosinophils per high-power field, favoring a diagnosis of eosinophilic esophagitis. The hiccups resolved following the initiation of eosinophilic esophagitis treatment. Conclusion This case underscores the need to consider the diagnosis of eosinophilic esophagitis in the setting of chronic refractory hiccups.